Perioperative outcomes and survival following neoadjuvant stereotactic body radiation therapy (SBRT) versus intensity‐modulated radiation therapy (IMRT) in pancreatic adenocarcinoma. Issue 5 (15th February 2018) - Chapman, Brandon C.; Gleisner, Ana; Rigg, Devin; Meguid, Cheryl; Goodman, Karyn; Brauer, Brian; Gajdos, Csaba; Schulick, Richard D.; Edil, Barish H.; McCarter, Martin D.
Abstract : Background and Objectives: To compare outcomes in patients receiving neoadjuvant stereotactic body radiation therapy (SBRT) with those receiving intensity‐modulated radiation therapy (IMRT) for pancreatic adenocarcinoma. Methods: We analyzed patients receiving neoadjuvant SBRT for borderline resectable (BRPC) and locally advanced pancreatic cancer (LAPC) (2012‐2016). Differences in baseline characteristics, perioperative outcomes, progression‐free survival (PFS), and overall survival (OS) were compared. Results: Seventy‐five (82.4%) patients received SBRT and 16 (17.6%) received IMRT. There were no differences in surgical resection rates in the SBRT ( n  = 38, 50.7%) and IMRT ( n  = 11, 68.8%) groups ( P  = 0.188). Among resected patients, there was no difference in postoperative outcomes or pathologic outcomes including lymph node status, margin status, lymphovascular and perineural invasion, or pathologic response to neoadjuvant treatment ( P  > 0.05). Among all patients, median PFS and OS were 9.9 and 23.5 months in the SBRT group, respectively, and 15.3 and 21.8 months in the IMRT group, respectively ( P  > 0.05). Similarly, there was no difference in PFS or OS between groups when stratified by BRPC, LAPC, and surgically resected patients ( P  > 0.05). Conclusions: In the neoadjuvant setting, SBRT and IMRT appear to have similar rates of resection, perioperative outcomes, and survival outcomes, but additional studies with increased sample size and longer follow up are needed.